IMPACTOS DA PANDEMIA EM ENTIDADES SEM FINS LUCRATIVOS - MARIS ENDERLI , STELA; CARLOS RASIA , PEDRO; MARGARETE BACCIN BRIZOLLA , MARIA; BASSO , LAURÍ; NEY KUHN , IVO; TEIXEIRA PINTO , THAÍS (Salão do Conhecimento, 2021)
Projeto Gestão Social e Cidadania